One single-center cross-sectional investigation on varicella antibody level of all age groups in Chinese people - Qing-Hong Meng; Xiao-Ping Cheng; Dan-Dan Liu; Chang-Hui Chen; Kai-Hu Yao (Taylor & Francis Group, 2021)
Varicella outbreaks were mainly reported in developed regions with high vaccine coverage, but not in undeveloped areas. It is still not clear that whether the published data of varicella epidemiology could reflect the reality in China or not. In 2019, 657 subjects from People's Hospital of Chongqing Youyang County were included. Anti-varicella-zoster virus (VZV) IgG antibodies were determined by ELISA. The anti-VZV IgG levels were categorized as positive when values were ≥100 mIU/mL. Our results showed that the rates of anti-VZV IgG seropositivity (χ2 = 328.957, P < .0001) and geometric mean titers (P < .0001) were significantly influenced by age. The seropositivity declined dramatically from 84.5% in subjects ≤3 m of age, to 7.9% in subjects of >3 m-1 y (P < .0001). Then, the positivity rate increased slowly as age to 26.7% in >1-<3 y (P = .0006), and 34.5% in 3-<7 y (P = .4294). A steady rise (45.6%) in positivity was observed in subjects aged 7-<18 y. After then, the positivity began to increase robustly. A total of 87.8% of adults aged 18-<40 y had acquired VZV-specific immunity (P < .0001). The highest positivity rate was found in 40-<60 y  (98.3%) and ≥60 y (98.2%) group. In conclusion, most subjects of >3 m-<7 y age were susceptible to VZV. The proportion of subjects with natural infection-induced immunity increased with age. Nearly all subjects over 40 ages had positive anti-VZV IgG antibodies, which proved that they were infected by this virus in the past. These results suggested that VarV should be included in the national immunization program in China.